2012
DOI: 10.1152/ajpheart.01026.2011
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of anticoagulant proteins, protein S and tissue factor pathway inhibitor, in the mouse myocardium with cardio-specific TNF-α overexpression

Abstract: Heart failure (HF) has been recognized as a hypercoagulable state. However, the natural anticoagulation systems in the failing heart have not been studied. Recent experimental and clinical data have indicated that not only the thrombomodulin (TM)/protein C (PC) pathway but also the protein S (PS)/tissue factor pathway inhibitor (TFPI) system function as potent natural anticoagulants. To investigate the balance between procoagulant and anticoagulant activities in the failing heart, we measured the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
(55 reference statements)
1
10
1
Order By: Relevance
“…Tyro3 predominates in mouse and human central nervous systems (CNS) [16,17], but it is also expressed by platelets [18], the heart [19], ovaries and testis [20], breasts [21], osteoclasts [22], and the retina [23]. Axl is widely expressed in many tissues and organs, including the brain [24], liver [25], kidney [26], heart [19], monocytes/macrophages [27], and endothelial [28] and vascular smooth muscle cells [29].…”
Section: The Gas6/tam Receptors Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyro3 predominates in mouse and human central nervous systems (CNS) [16,17], but it is also expressed by platelets [18], the heart [19], ovaries and testis [20], breasts [21], osteoclasts [22], and the retina [23]. Axl is widely expressed in many tissues and organs, including the brain [24], liver [25], kidney [26], heart [19], monocytes/macrophages [27], and endothelial [28] and vascular smooth muscle cells [29].…”
Section: The Gas6/tam Receptors Systemmentioning
confidence: 99%
“…Tyro3 predominates in mouse and human central nervous systems (CNS) [16,17], but it is also expressed by platelets [18], the heart [19], ovaries and testis [20], breasts [21], osteoclasts [22], and the retina [23]. Axl is widely expressed in many tissues and organs, including the brain [24], liver [25], kidney [26], heart [19], monocytes/macrophages [27], and endothelial [28] and vascular smooth muscle cells [29]. Finally, MerTK is the main mediator of Gas6 activity on immune cells [30,31], but is also expressed by the brain [24], platelets [32], gonads and prostate [33,34], lung [35], retina [23], kidney [36], and heart [19].…”
Section: The Gas6/tam Receptors Systemmentioning
confidence: 99%
“…It has been postulated using animal models such as the murine system that increase in the anticoagulation parameters is a protective mechanism in heart failure in the setting of hypercoagulable and pro inflammatory states [17]. The other explanation for increased anticoagulation is the dysfunction of the right ventricle and passive congestion of the liver that follows.…”
Section: Discussionmentioning
confidence: 99%
“…20 -22 Higuchi et al 23 found that protein S was upregulated in mouse myocardium in different aetiological models of HF, and hypothesized that this up-regulation may have a protective role in the failing heart. 23 A recent review by Mongirdiene et al 22 highlighted coagulation factors V and VII as being altered in HF; however, the roles in HF of coagulation factors IX and X, from the RHF biomarker panel, are presently unclear. The enrichment of coagulation-related proteins in the RHF panel suggests that this pathway could well play a much larger role in HF, particularly in protective or recovery processes, than currently thought.…”
Section: Discussionmentioning
confidence: 99%